Tumor genetics and survival of thymic neuroendocrine neoplasms: A multi‐institutional clinicopathologic study. Issue 9 (25th April 2014) - Ströbel, Philipp; Zettl, Andreas; Shilo, Konstantin; Chuang, Wen‐Yu; Nicholson, Andrew G.; Matsuno, Yoshihiro; Gal, Anthony; Laeng, Rolf Hubert; Engel, Peter; Capella, Carlo; Marino, Mirella; Chan, John Kwok-Cheung; et al.
<x xml:space="preserve">Abstract</x> Thymic neuroendocrine tumors (TNET) are rare primary epithelial neoplasms of the thymus. This study aimed to determine clinically relevant parameters for their classification and for therapeutic decisions. We performed a comprehensive histological, clinical, and genetic study of 73 TNET cases (13 thymic typical carcinoids [TTC], 40 thymic atypical carcinoids [TAC], and 20 high‐grade neuroendocrine carcinomas [HGNEC] of the thymus), contributed by multiple institutions. The mean number of chromosomal imbalances per tumor was 0.8 in TTC (31% aberrant cases) versus 1.1 in TAC (44% aberrant cases) versus 4.7 in HGNEC (75% aberrant cases). Gains of 8q24 (MYC gene locus) were the most frequent alteration and one of the overlapping features between carcinoids and HGNEC. The 5‐year survival rates for TTC, TAC, and HGNEC were 100, 60, and 30%. The 10‐year survival rates for TTC and TAC were 50 and 30% (P = 0.002). Predictive mitotic cut‐off values for TTC versus TAC were 2.5 per 10 high‐power fields (HPF; indicating a higher death rate, P = 0.062) and 15 per 10 HPF (indicating higher risk of recurrence, P = 0.036) for separating HGNEC from TAC. We conclude that the current histopathologic classifications of TNET reflect tumor biology and provide important information for therapeutic management. © 2014 Wiley Periodicals, Inc.